Restructuring in higher education institutions: a case study of centralised cleaning services at Rhodes University - Ntlokwana, Ziyanda (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
The centralization of cleaners at Rhodes University has been the university's response to the pressures put on higher education. This form of restructuring is the university's attempt at dealing with the government's cuts in funding despite the increasing demands placed on higher education institutions. The demands on universities necessitates that they compete on a global scale ,which sometimes sees many universities adopting a 'neoliberal logic' and as a result cutting labour costs to survive and compete. The aim of this study was to examine the nature and form of restructuring at Rhodes University and its impact on the workers' lives. This research made use of both quantitative and qualitative research methods: namely, a quantitative survey that focused on the cleaners and in-depth interviews with trade union representatives. This research discovered that the restructuring programme at Rhodes University is different from that at other universities through its avoidance of outsourcing and the retrenchment of workers. Despite this tricky balance, however, the effects of this form of restructuring largely embody outsourcing characteristics and as a result disadvantage the cleaners.
Keywords: Uncatalogued